The Silence Painter: A New “Name” in the History of the Kerch Style Vase-Painting - Vas’ko, Dmitrii S. (Actual Problems of Theory and History of Art, 2017)
The article attempts to identify a new vase-painter. In his works he usually didn’t even mark the mouths of the figures on the B-sides of the vessels; therefore we suggest calling him the Silence Painter. Here enumerated are 20 pelikai, including a fragmented one, that were supposedly painted by him. The vessels were divided into four groups according to their size and subjects. Some of the subjects are discussed in detail. The Silence Painter worked in the middle — the third quarter of the 4th century BCE. Some of his vessels were discovered in Olynthus, Lesbos and Karia, but the main customers lived in the North Pontic region, where fifteen pelikai were found. Their subjects and compositions are typical for the Kerch style. The Silence Painter was a mediocre craftsman, who used themes and designs that had been already invented by his predecessors.
Keywords: attribution; vase-painting; the Kerch style; pelike; Dionysus